Did RSPO overlook the unwelcome thoughts amongst growers and millers? - Lee, Kim Huat; Julian Paul Sidin,; Stephen Laison Sondoh Jr., (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study examined the relationship between knowledge, past experience and personal value of growers and millers intention to adopt the RSPO. This study applied the theory of Planned Behaviour (TPB) to test the proposed relationship. This research applies a quantitative approach that uses a cross-sectional questionnaire survey in order to test the proposed hypotheses. A total of 122 palm oil companies in Sabah, Malaysia were identified and collected data were analysed using the partial least squares and structural equation modelling. The findings of this study confirmed the Theory of Planned Behaviour as a great predictor of behavioural intention. In addition, knowledge, past experience and personal value were also found to have significant relationship and this resulted into the conclusion that knowledge, past experience and personal value positively influence the attitude amongst growers and millers towards RSPO. The result of this study has proven that the TPB model is a valuable, practical and has a high potential to predict human behavioural intention.